Historical background of surgical treatment of lung cancer in the elderly - Humańska, Marzena Agnes; Ulenberg, Agata; Ulenberg, Gregory; Pluta, Agnes; Półrolnik, Christine; Felsmann, Miroslaw (Journal of Education, Health and Sport, 2018)
The history of treatment of lung metastases with surgical resection is over 120 years old. For many years it was believed That all attempts at surgical treatment were ineffective and even harmful. It took many years of research prove That is a surgical treatment is often the only way to give patients a chance to prolong this life and even permanent cure. Lobectomy together with pneumonectomy is the most commonly performed procedures in lung cancer.